Fundamentals of soil ecology - Coleman, David C. 1938-; Callaham, Mac A.,Jr; Crossley, D. A. (Elsevier, 2018)
Fundamentals of Soil Ecology, 3rd Edition, offers a holistic approach to soil biology and ecosystem function, providing students and ecosystem researchers with a greater understanding of the central roles that soils play in ecosystem development and function. The text emphasizes the increasing importance of soils as the organizing center for all terrestrial ecosystems and provides an overview of theory and practice in soil ecology, both from an ecosystem and evolutionary biology point of view. This new edition is fully updated, including an expanded treatment of microbial ecology and new sections on advances in molecular techniques and climate change research. These updates make this edition an essential resource for researchers and students in soil ecology and microbiology.--Provided by publisher.